Zinc Sulfate Foliar Application Effects on Some Physiological Characteristics and Phenolic and Essential Oil Contents of Lavandula stoechas L. Under Sodium Chloride (NaCl) Salinity Conditions. Issue 16 (8th September 2017) - Vojodi Mehrabani, Lamia; Kamran, Rana Valizadeh; Hassanpouraghdam, Mohammad Bagher; Pessarakli, Mohammad
ABSTRACT: Lavandula stoechas L. plant is a perennial evergreen used as a fragrant ornamental and medicinal plant. In order to study the effect of foliar spray of zinc sulfate (ZnSO4 ) (0, 1000, and 2000 mgL −1 ) and sodium chloride (NaCl) salinity (0, 75, and 150 mM) on some physiological characteristics of Lavandula stoechas L. plants, a pot experiment was carried out at the Research Greenhouse of Azarbaijan Shahid Madani University, Iran. Physiological characteristics [root and leaf dry weights, total soluble solids (TSSs), total anthocyanins, chlorophyll b, Zn 2+, potassium (K + ) contents, and K + /Na + ratio] were significantly affected by the interaction effects of ZnSO4 foliar application and salinity levels. The highest root dry weight, chlorophyll b, anthocyanin, and Zn contents as well as TSS were found in the plants with NaCl0 × ZnSO4 2000 mgL −1 . For Na +, the greatest value was recorded with NaCl150 × ZnSO40 . The highest K + /Na + ratio was found in the control plants. Foliar application of ZnSO4 promoted the total phenolic content, especially at 2000 mgL –1 . The highest amounts of flower dry weights were recorded at NaCl0 . Chlorophyll a, total flavonoids, stem dry weight, and essential oil content were affected with ZnSO4 treatment and salinity levels. The highest values for the essential oil content, chlorophyll a content, and stem dry weight were attained by the nonsaline treatment. Both foliar application levels positively influenced the essential oil and flavonoid contents of the plants. The results reveal that zinc application had marked effects on the physiological characteristics of Lavandula stoechas L. plants growing under salinity stress conditions.